Goodman versus Rawls: Politics, Philosophy, and Theology. Issue 6 (30th October 2015) - Novak, David
Abstract : Lenn Goodman's book, Religious Pluralism and Values in the Public Sphere, 1 is a tour de force, challenging the most important liberal thinker of the past 50 years, the late John Rawls. In this book, Goodman challenges Rawls' political intolerance of religious voices, Rawls' anti-metaphysical philosophy, and Rawls disdain for theology. The author basically agrees with Goodman's political critique, and mostly agrees with his philosophical position. The difference between Goodman and the author lies in the different schools of thought in Jewish theology to which each of them ascribes. That difference is especially seen in their differing approaches the question of revelation.